PENGARUH MENONTON KARTUN TOM AND JERRY TERHADAP PERILAKU AGRESIVITAS ANAK USIA 3-4 TAHUN - Mazidah, Rohmatun; Reza, Muhammad (PAUD Teratai, 2016)
Abstract : This research has a purpose to determine whether there is effect of watching Tom and Jerry cartoons to the aggressive behavior early childhood 3-4 years old. While the approach used in this study using a quantitative approach with the methods of Experiment with Post test two groups using a statistical design with non-parametric Mann-Whitney U-Test. The subject of this research is all of the children 3-4 years old at PAUD Al-Abror Pamekasan namely 30 subjects.the result of this result show that U count value is smaller than the U value tableU hitung < U table (173,5 < 3,733), then the hypothesis (Hi) proposed that: